Na primeira série aos seis anos: as experiências das crianças/alunas e da professora/pesquisadora no ambiente escolar - Matsuzaki, Juliana Wild do Vale (2009)
The dissertation presents the results of a research developed with a group of first grade children of a public school located in the north suburbs of São Paulo city. The research intended to investigate children's experiences at the beginning of the elementary-school, according to the legal changes introduced since 2006, that anticipated this admission to 6 years old children. The research was accomplished throughout the school year in 2008 and the researcher was the teacher responsible for that group of children, who assumed a double role. The collected data consists of a logbook in which the children s experiences and speech were registered in intervals of a week and the transcription of a collective interview realized with a small group of children at the end of the year. Data was analysed with the support of the following categories: time, space, subjects/course, reading and writing. The results reveal interesting aspects about the transition experienced by children such as their new role as students, their feeling about differences between kindergarten and elementary school, as well as their view about new obligations like homework, writing tasks and the use of the notebook. Besides that, data shows their need for larger playing spaces and their complaints about the tiredness that goes along with the new duties fulfillment. The paper reflects about all those questions based on the approach of the Sociology of Childhood and discusses the importance of listening to children about their experience on the transition from kindergarten to elementary school one year earlier than it used to be